Empowering the online distance learning using Gamification / Anisah Abdul Rahman … [et al.] - Abdul Rahman, Anisah; Shaffie, Siti Salihah; Ibrahim, Ireen Munira; Ismail, Siti Rozanae; Najmuddin, Ahmad Farid (Faculty of Computer and Mathematical Sciences, 2021)
Online distance learning began to be fully practiced when the Covid-19 pandemic hits the rest of the world. The education sector, including higher education was also affected by this unfortunate event. However, to ensure teaching can be delivered to the students as effective as possible, changes are required to be done. There are numerous modern teaching methods and techniques are used to fit the needs of teaching and learning. Gamification is one of the popular approaches that can be used to improve teachings, and with the aid of several available tools, it can promote engaging learning experience to the students. This study utilises 3 gamification tools that are used in one of mathematical course, namely Quizziz, Oodlu and Socrative. The exposure of gamification to the students is vital to develop sense of responsibility towards learning and facilitate the learning process in an engaging digital environment.